Separação sólido-fluido de perfuração em peneiras vibratórias - Nascentes, Cleuton Luis (2019)
The primary objective of the drilling solids control system is to recover the fluid for reuse and discard drilling solids with the minimum adhered fluid content. The use of shale shakers for drilling solid-fluid separation is of great importance for the entire solids control system. The simulation of mathematical models representative of solid- drilling fluid separation in shale shakers is of great help in observing the phenomena involved in the separation. Through simulation it is possible to observe the influence of different parameters on the separation efficiency without the need to perform a large number of experimental tests. Optimal adjustment of operating parameters in shakers contributes to drilling fluid recovery and extends the life of the screens. Simulating the modeling of the drilling fluid flow dynamics on the vibrating screen is an important step to obtain control strategies aiming at an efficient separation operation. Simulated and experimental results of the drilling fluid flow over the screen of a vibrating screen in steady and transient regimes are presented in this work. The experimental results indicate that the model can be used to evaluate the effect of disturbances and it offers opportunities to implement model based process control strategies in shale shakers.